The Urgency of Providing Village Library Services in Increasing Village Community Literacy and Creating Quality Human Capital - Susilawati, Susilawati; Marlina, Marlina; Ilmi, Khilwa; Gunawan, Anak Agung Ngurah; Zulham, Zulham (Journal Of Human And Education (JAHE), 2024)
Lakkang Village is one of the villages in Tallo District, Makassar City, South Sulawesi. Lakkang Village is geographically located in the middle of the Makassar urban area, its location is in the delta of the Tallo and Pampang rivers, which are one of the rivers that divide Makassar City. The current problem faced by Lakkang village is the problem of low literacy or interest in reading, this is caused by a lack of public awareness about interest in reading and writing, even though if you look back at reading and writing skills, known as literacy, it is the main basis for efforts to improve community education level. One effective strategy to advance literacy culture is through the development of libraries, especially in villages. To overcome this problem, an alternative solution that can be implemented is to carry out activities to improve village library services to realize increased literacy in village communities so that it is hoped that they can create quality human resources in Lakkang Village, Tallo District, Makassar City, South Sulawesi. Therefore, the aim of this community service is to see the potential for improving village library services in realizing increased literacy in the community in Lakkang Village, Tallo District, Makassar City, South Sulawesi. To obtain the data used were observation and literature review. This service activity is an educational effort to improve village library services which are able to realize literacy in Lakkang Village, Tallo District, Makassar City, South Sulawesi. As a form of the author's thinking, several efforts and breakthroughs are offered, namely: 1.) Increasing community knowledge regarding literacy by improving village library services, 2.) The role of improving village library services for the Lakkang Village community in realizing increased interest in reading and writing in the village is to create quality human resources.